Pengembangan Interpersonal Intelligence Pada Peserta Didik Kelas VB MI Ma’arif Surotrunan - Laeli Parwati; Oky Ristya Trisnawati (Tarbi: Jurnal Ilmiah Mahasiswa, 2026)
This research aims to determine the teacher's efforts in developing interpersonal intelligence for the VB MI Ma'arif Surotrunan class, to determine the supporting factors and inhibiting factors in developing interpersonal intelligence. This type of research is descriptive research. The subjects of this research were the principal, teachers and students of the VB MI Ma'arif Surotrunan class. The object of this research is the teacher's efforts to develop interpersonal intelligence. The research location was MI Ma'arif Surotrunan. The method used to collect data is observation, interviews and documentation. Data analysis was carried out using data reduction, data presentation and drawing or verifying conclusions. The research results show that students' interpersonal intelligence is in the low category. From the research results, it is known that several interpersonal intelligence problems occur among students, namely that students are not reluctant when the teacher explains learning material and the number of boys in the class is more than the number of girls. Apart from that, students who experience interpersonal intelligence problems tend to be absorbed in their own world and their parents' parenting patterns influence the development of students' interpersonal intelligence.